Feasibility of the application of frequency modulated continuous wave radar trigger technique in abdominal magnetic resonance imaging - Song, Qingling; He, Yongquan; Chen, Lihua; Xia, Xinyuan; Wang, Nan; Song, Qingwei; Liu, Ailian (Frontiers in Physics, 2024)
Objective: To evaluate and compare the image quality of T2-weighted abdominal scans using Belt Respiratory-Trigger (BRT) and Frequency Modulated Continuous Wave (FMCW)-Trigger (FT) techniques, and to explore the feasibility of FT in abdominal magnetic resonance imaging (MRI). Methods: The study prospectively included 28 subjects, each undergoing abdominal scans with both BRT and FT. Analysis focused on 64 inconsistent trigger segments from the respiratory curves triggered by BRT and FMCW. Parameters such as Inconsistent Trigger Type (ITT), Number of Inconsistent Trigger Points (ITP), Ratio of ITP (ITR), and Single Segment ITR (SITR) were derived from these curves. Image quality was evaluated by two observers using subjective scoring, Signal-to-Noise Ratio (SNR), and Contrast-to-Noise Ratio (CNR). The assessments classified image quality as either 'good' or 'poor'. Consistency in image quality assessment between observers was determined using the Kappa test and Intraclass Correlation Coefficient (ICC). The Chi-square test, Student's t-test, and Mann-Whitney U test were employed to compare the categorical and continuous variables between the BRT and FT groups. Results: The observers showed a high level of agreement in image quality assessment. There were no significant differences in ITR, SITR, acquisition time, SNR, and CNR between the BRT and FT groups (all P>0.05). Both subjective and objective evaluations indicated no notable difference in image quality between the two groups (P>0.05). Conclusions: The FMCW-trigger technique is a viable alternative to the traditional belt respiratory-trigger in scenarios of relatively stable breathing. It offers potential benefits, such as reducing operational demands on technicians and improving MRI workflow efficiency.